Pengaruh Thawing terhadap Kualitas Semen Kambing Boer Menggunakan Pengencer Tris-aminomethane yang Disuplementasi Antioksidan Quercetin - Sari, Rossa Purnama; Nugraha, Chairdin Dwi; Suyadi, Suyadi (Universitas Bengkulu, 2024)
This study aims to determine the effect of the thawing technique on the quality of Boer goat semen with tris aminomethane diluent supplemented with quercetin antioxidants. The materials used in this research are the semen of a Boer goat, which was collected with an artificial vagina. This study used experimental laboratory methods. The design pattern used is a Factorial Complete Randomized Design, which consists of two factors. Each treatment was repeated 4 times. The first factor is the thawing temperature with 3 levels of treatment those were 32°C, 37°C, and 40°C. The second factor is the thawing time with 3 treatment levels: 30 seconds, 60 seconds and 90 seconds. The variables were the motility percentage, viability, abnormality and membrane integrity. The results showed that thawing temperature had a significantly different effect (P<0.01) on the percentage of motility, viability, abnormality and membrane integrity. Thawing time had a significantly different effect (P<0.01) on the percentage of motility, abnormality and membrane integrity and gave affects significant (P<0.05) in the percentage of viability. Meanwhile, the interaction between thawing temperature and time is insignificant (P>0.05). The best result shown after thawing is in treatment thawing temperature at 37°C and treatment thawing time at 30 seconds.